2001 Proceedings. 51st Electronic Components and Technology Conference (Cat. No.01CH37220)
DOI: 10.1109/ectc.2001.927927
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lead(Pb)-free ceramic ball grid array (CBGA): Wettability, microstructure and reliability

Abstract: Flip-chip carriers have become the preferred solution for high-performance ASIC and microprocessor devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…More than 70% market for reflowing lead-free solders are in the SAC series. Due to having good mechanical properties, acceptable wetting properties, and suitable melting points, the International Printed Circuit Association has suggested that SAC-305 and SAC-396 will be the most widely used alloys in the future [10][11][12][13][14][15][16].…”
Section: Sac305mentioning
confidence: 99%
See 1 more Smart Citation
“…More than 70% market for reflowing lead-free solders are in the SAC series. Due to having good mechanical properties, acceptable wetting properties, and suitable melting points, the International Printed Circuit Association has suggested that SAC-305 and SAC-396 will be the most widely used alloys in the future [10][11][12][13][14][15][16].…”
Section: Sac305mentioning
confidence: 99%
“…More than 70% market for reflowing lead-free solders are in the SAC series. Due to having good mechanical properties, acceptable wetting properties, and suitable melting points, the International Printed Circuit Association has suggested that SAC-305 and SAC-396 will be the most widely used alloys in the future [10][11][12][13][14][15][16].Although SAC-305 alloy is widely used in electronics industry, it has several problems to be solved. One of the core issues pertaining to Abstract Sn96.5Ag3Cu0.5 (SAC305) is widely used as lead-free solder for surface mount technology (SMT) card assembly and for ball-grid-array (BGA) interconnection in the microelectronic packaging industry as solder balls and pastes.…”
mentioning
confidence: 99%
“…However, a recent study has found that the addition of the nanoparticle size of Fe and Al 2 O 3 in SAC solder alloys can improve mechanical properties because of the formation of FeSn 2 intermetallic compounds and Al 2 O 3 nanoparticles serving as a grain refiner [3]. In the microelectronics packaging industry, SAC alloys are widely used as solder pastes in connecting chip parts and ball grid arrays (BGAs) [4]. Lead-free solder powders which are used in microelectronics applications strictly require high product qualities such as spherical shape, low oxygen content (~100 ppm), and narrow size distribution [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among various alloy systems that are considered as lead-free solder candidates, Sn-Ag-Cu alloys have been recognized as the most promising because of their relatively low melting temperature (compared with the Sn-Ag binary eutectic leadfree solder), superior mechanical properties, and good compatibility with other components [1][2][3]. Sn-Ag-Cu alloys are widely used as lead-free solutions for ball-grid-array (BGA) interconnection in the microelectronic packaging industry as solder balls and pastes [4].…”
Section: Introductionmentioning
confidence: 99%